2023
DOI: 10.1038/s41598-023-42710-0
|View full text |Cite
|
Sign up to set email alerts
|

The long-term impact of the COVID-19 pandemic on physical fitness in young adults: a historical control study

Jeffrey W. Ripley-Gonzalez,
Nanjiang Zhou,
Tanghao Zeng
et al.

Abstract: The strength of evidence regarding long-term changes to fitness resulting from the coronavirus disease 2019 (COVID-19) lockdowns is deficient. This two-site retrospective study aimed to investigate the long-term changes in physical fitness among young adults a year after the onset of the pandemic using a robust historical control. University freshmen who underwent physical fitness tests in 2019 and completed a follow-up in 2020 (study group) were included. The primary focus was to compare the current cohort wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 36 publications
0
1
1
Order By: Relevance
“…Our results also indicated that online teaching can also maintain or improve most fitness indicators. This finding is not consistent with previous studies [ [33] , [34] , [35] ]. Previous studies have shown that the physical fitness of college students has declined overall during the COVID-19 pandemic, but we found online teaching seems to maintain effect on most physical fitness indicators.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results also indicated that online teaching can also maintain or improve most fitness indicators. This finding is not consistent with previous studies [ [33] , [34] , [35] ]. Previous studies have shown that the physical fitness of college students has declined overall during the COVID-19 pandemic, but we found online teaching seems to maintain effect on most physical fitness indicators.…”
Section: Discussioncontrasting
confidence: 99%
“…In the years during and after the SARS-COVID-19 pandemic, many effects on physically active people were studied. Over the years both the long- and the short-term effects were studied [ 7 , 8 , 9 ]. Professional athletes and organized club sports in particular allowed systematic studies to be carried out [ 2 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%